2021
DOI: 10.1039/d1ma00217a
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of non-covalent interactions in unexpectedly high and selective CO2 uptake and catalytic conversion of porphyrin-based ionic organic polymers

Abstract: Here, we present the viologen-porphyrin based ionic covalent organic polymers (H2-ICOP and Zn-ICOP) with multiple CO2-philic sites. The specific surface areas of H2-ICOP and Zn-ICOP were found to be 9...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…The rational design and controllable synthesis of functional solid networks is one of the fundamental goals of materials science and crystal engineering. 1,2 Within the toolbox of crystal engineering, various weak non-covalent interactions have been utilized to connect molecular building blocks to achieve ordered network materials for gas storage, 3 separation, 4 catalysis, 5 and optoelectronic 6 applications. In this regard, weak but directional supramolecular interactions, such as hydrogen/halogen bonding and stacking interactions, could be a good alternative to robust metal–carbon coordinate bonds.…”
mentioning
confidence: 99%
“…The rational design and controllable synthesis of functional solid networks is one of the fundamental goals of materials science and crystal engineering. 1,2 Within the toolbox of crystal engineering, various weak non-covalent interactions have been utilized to connect molecular building blocks to achieve ordered network materials for gas storage, 3 separation, 4 catalysis, 5 and optoelectronic 6 applications. In this regard, weak but directional supramolecular interactions, such as hydrogen/halogen bonding and stacking interactions, could be a good alternative to robust metal–carbon coordinate bonds.…”
mentioning
confidence: 99%
“…According to the concept of the dual activation model of epoxide, the molar ratios of metal centers and halogen anions were very important for enhanced CO 2 uptake and catalytic conversion, but it has been ignored by many researchers. 25,32,38,52 The content of halogen anions can be calculated from the amount of nitrogen element determined by CHN analysis 24,40 or directly measured by IC analysis. 53 The latter would be more accurate than the former.…”
Section: Catalytic Performance Of Catalystsmentioning
confidence: 99%
“…For example, SYSU-Zn@IL2 was constructed by the Schiff-base condensation reaction using zinc(II) 5,10,15,20-tetrakis(4-aminobiphenyl)porphyrin and aldehyde-functionalized ILs (Table 3, entry 1), 38 and Zn− ICOP was synthesized from the Zincke reaction of viologen Zincke salt and zinc(II) 5,10,15,20-tetrakis(4-aminophenyl)porphyrin (Table 3, entry 2). 32 Both of them presented fairly low surface areas (about 20 m 2 g −1 ) and low-to-moderate CO 2 uptakes, thus achieving low TOF values at 80 °C and 10 bar. However, it is worth noting that the uniform local structures endow them to possess identical catalytic microenvironments.…”
Section: Catalytic Performance Of Catalystsmentioning
confidence: 99%
“…[61] Recently, Ayhan et al reported efficient catalytic activity of viologen-porphyrin-based iCOPs due to the presence of multiple CO 2 -philic sites and efficient non-covalent interactions with CO 2 . [62] Charged Covalent Triazine Frameworks (cCTFs) CTFs are nitrogen-rich porous structures with ultra-strong aromatic C=N linkages. CTFs are versatile materials for heterogeneous catalysis owing to their high specific surface area with adjustable pore size, designable surface-active sites, and exceptional physicochemical stability.…”
Section: Ionic Covalent Organic Polymers (Icops)mentioning
confidence: 99%